Validation of Lipophosphonoxin-loaded Polycaprolactone Nanofiber Dressing for Full-thickness Wounds in a Porcine Model - ŠUCA, HUBERT; JUHÁS, ŠTEFAN; JUHÁSOVÁ, JANA; JENČOVÁ, VĚRA; KOŠŤÁKOVÁ, EVA KUŽELOVÁ; LUKÁŠ, DAVID; BOHUŠ, PETER; BALLOVÁ, ZUZANA; ZAJÍČEK, ROBERT; REJMAN, DOMINIK; GÁL, PETER (In vivo (Athens), 2025)
This study investigated the therapeutic potential of lipophosphonoxin (LPPO), an antibacterial agent, loaded into polycaprolactone nanofiber dressings (NANO-LPPO) for full-thickness wound healing. Using a porcine model, we aimed to assess the impact of areal weight of the dressing (10, 20 and 30 g/m ) on wound-healing outcomes and validate findings from previous murine studies. Full-thickness wounds were created on porcine skin and treated with the NANO-LPPO dressings of differing thickness. Positive control (Aquacel Ag+) and standard control (Jelonet) groups were included for comparison. Wound-healing progression was evaluated macroscopically and on the histological level. Macroscopic observations indicated no signs of infection in any group, with wounds covered by scabs by day 14. Thicker dressings (areal weights of 30 and 20 g/m ) demonstrated superior performance in promoting the formation of granulation tissue and healing compared to the thinner version (areal weight of 10 g/m ). LPPO-loading enhanced scaffold wettability and biodegradability without impairing healing outcomes. Both control groups exhibited similar healing characteristics. The findings underscore the importance of optimizing dressing thickness for effective wound healing. NANO-LPPO dressings exhibit translational potential as a therapeutic option for full-thickness wounds, warranting further preclinical and regulatory evaluation to support clinical application.